Face Mask Contribution in Improving Students' Confidence in English Speaking Class - Fitriany , S.S., M.Hum.; Nur Fauziah ,SS.,M.Hum (Journal of Language, Literature and Teaching, 2022)
This article aims to reveal the outcome of the new normal habit of wearing face mask and its contribution in boosting or improving students’ self confidence in speaking English. The habit which was once forced as the token of keeping someone healthy and to break the spreading of corona virus -19 disease during the pandemic turns out to be a bless in disguise. The subdue of the pandemic is the good news to educators as well as students. Teaching and learning activities conducted from home has raised other issues regarding the behavior and mental health of students. The restriction in socializing bored the students. The opening of schools and allowing students and teachers have interaction during the teaching and learning activities is followed by health protocols, one of them is wearing face mask. Face mask is obligatory. The reluctance and the awkwardness in wearing the face mask in the beginning has become the reluctance and awkwardness in taking the mask off. Students in English speaking classroom admit the fact that they feel more comfortable and more confidence expressing themselves during presentation or speech delivering with their masks off when the wearing of face mask is no longer obligatory.The approach of this writing is descriptive qualitative. Observations, field notes and interview were conducted to eighty-one high school students who use English as their second language at school. The finding is surprising. Twenty-five percent of the students claim that their self-confidence improve when they wear mask during class presentation.